Pollinator‐mediated assemblage processes in California wildflowers. (4th March 2016) - Briscoe Runquist, R.; Grossenbacher, D.; Porter, S.; Kay, K.; Smith, J.
Abstract: Community assembly is the result of multiple ecological and evolutionary forces that influence species coexistence. For flowering plants, pollinators are often essential for plant reproduction and establishment, and pollinator‐mediated interactions may influence plant community composition. Here, we use null models and community phylogenetic analyses of co‐occurrence patterns to determine the role of pollinator‐mediated processes in structuring plant communities dominated by congeners. We surveyed three species‐rich genera ( Limnanthes, Mimulus and Clarkia ) with centres of diversity in the Sierra Nevada of California. Each genus contains species that co‐flower and share pollinators, and each has a robust phylogeny. Within each genus, we surveyed 44–48 communities at three spatial scales, measured floral and vegetative traits and tested for segregation or aggregation of: (i) species, (ii) floral traits (which are likely to be influenced by pollinators), and (iii) vegetative traits (which are likely affected by other environmental factors). We detected both aggregation and segregation of floral traits that were uncorrelated with vegetative trait patterns; we infer that pollinators have shaped the community assembly although the mechanisms may be varied (competition, facilitation, or filtering). We also found that mating system differences may play an important role in allowing species co‐occurrence. Together, it appears that pollinators influence community assemblage in these three clades.